2017
DOI: 10.1055/s-0037-1601351
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Mechanisms of Liver Regeneration

Abstract: Liver possesses many critical functions such as synthesis, detoxification, and metabolism. It continually receives nutrient-rich blood from gut, which incidentally is also toxin-rich. That may be why liver is uniquely bestowed with a capacity to regenerate. A commonly studied procedure to understand the cellular and molecular basis of liver regeneration is that of surgical resection. Removal of two-thirds of the liver in rodents or patients instigates alterations in hepatic homeostasis, which are sensed by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 86 publications
0
55
0
4
Order By: Relevance
“…In fact, Id1 ‐deficient mice also showed defective LR initiation that was associated with decreased expression of hepatocyte growth factor and Wnt2 in sinusoidal ECs. ECs and macrophages may be getting signals from cytokines, such as tumor necrosis factor α and interleukin‐6, which are not primary mitogens but are known to contribute to LR 34. Indeed, a recent study showed that stimulation of macrophages by tumor necrosis factor α induces nuclear factor kappa B activation, which then led to secretion of Wnts from these cells 35.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Id1 ‐deficient mice also showed defective LR initiation that was associated with decreased expression of hepatocyte growth factor and Wnt2 in sinusoidal ECs. ECs and macrophages may be getting signals from cytokines, such as tumor necrosis factor α and interleukin‐6, which are not primary mitogens but are known to contribute to LR 34. Indeed, a recent study showed that stimulation of macrophages by tumor necrosis factor α induces nuclear factor kappa B activation, which then led to secretion of Wnts from these cells 35.…”
Section: Discussionmentioning
confidence: 99%
“…HSCs also demonstrate remarkable ability to recruit inflammatory and immune cells, and influence their survival and functions (22,23,(38)(39)(40)(48)(49)(50)(51)(52)(53)(54). Furthermore, evidence has emerged showing an important role of HSCs in liver regeneration and hepatocellular carcinoma (55)(56)(57)(58). With these powerful characteristics, the strategically located HSCs regulate hepatic vascular tone, liver injury and regeneration, and hepatic immunological tolerance.…”
Section: Multifunctional Hepatic Stellate Cells (Hscs)mentioning
confidence: 99%
“…However, as the main detoxifying organ in the body, the liver has a high likelihood of toxic injury. 33,34 It is, therefore, not surprising that the liver has tremendous regenerative capacity. 33,35 This capacity distinguishes it from other vital organs (e.g., the brain, heart, and lungs) that are far less able to replace functional tissue when damaged.…”
Section: Inflammation As a Therapeutic Target For Chronic Liver Diseasementioning
confidence: 99%
“…33,34 It is, therefore, not surprising that the liver has tremendous regenerative capacity. 33,35 This capacity distinguishes it from other vital organs (e.g., the brain, heart, and lungs) that are far less able to replace functional tissue when damaged. Liver regeneration requires a tightly coordinated response to complement the regenerative process, so that the entire organ can be reconstituted.…”
Section: Inflammation As a Therapeutic Target For Chronic Liver Diseasementioning
confidence: 99%